Pengaruh Fasilitas Kamar Terhadap Kepuasan Tamu Menginap di Hotel Pesona Alam Sangir - Sari, Novella Yolanda; Manvi, Kurnia Illahi (JURNAL KAJIAN PARIWISATA DAN BISNIS PERHOTELAN, 2023)
This research aims to analyze the influence of room facilities on guest satisfaction staying at the Pesona Alam Sangir hotel. This research is quantitative descriptive research with a causal associative method. The method used in sampling is non probability sampling with a purposive sampling technique. The analysis techniques used in this research are validity test, reliability test, quantitative descriptive analysis, assumption test (normality test, linearity test, and coefficient of determination test). The sample used was guests staying at the Pesona Alam Sangir hotel. The results of the research show that: (1) Room facilities are in the quite good category overall with a percentage of (38%), (2) Guest satisfaction is in the quite good category overall with a percentage of (49%), (3) Linear regression test results simply obtained a calculated F value of 686.500 with sig 0.000 <0.05 then regression can be used. This means that room facilities have a significant effect on guest satisfaction. The results of the regression coefficient equation are 0.854 with sig. 0.000 < 0.05, meaning that every increase of 1 unit of room facilities will increase 1 unit of guest satisfaction. Then the R Square value is 0.762. This means that room facilities influence guest satisfaction by 76.2%, while 23.8% are influenced by other factors.